Effect of Three Roots tocks on Grapevine (Vitis vinifera L.) CV. Négrette, Grown Hydroponically. I. Potassium, Calcium and Magnesium Nutrition - Garcia, M.; Gallego, P.; Daverède, C.; Ibrahim, H. (South African Journal of Enology and Viticulture, 2017)
In order to study the lack of acidity in wines made out of cv. Negrette, a problem partially due to a high potassium content, this cultivar was grafted onto three different rootstocks, which were then grown in a nutrient solution.  Although cation nutrition varied as a function of the rootstock, the potassium level was high in leaves of all three rootstocks. Rootstock 3309 C induced the lowest potassium level. Furthermore, in combination with Negrette, SO 4 absorbed potassium more readily than 101-14 Mgt, contrary to the literature concerning other cultivars. To decrease the absorption of this element by Negrette, 3309 C appears to be the most appropriate rootstock.